2013
DOI: 10.3390/ijms141122618
|View full text |Cite
|
Sign up to set email alerts
|

Onjisaponin B Derived from Radix Polygalae Enhances Autophagy and Accelerates the Degradation of Mutant α-Synuclein and Huntingtin in PC-12 Cells

Abstract: Emerging evidence indicates important protective roles being played by autophagy in neurodegenerative disorders through clearance of aggregate-prone or mutant proteins. In the current study, we aimed to identify autophagy inducers from Chinese medicinal herbs as a potential neuroprotective agent that enhances the clearance of mutant huntingtin and α-synuclein in PC-12 cells. Through intensive screening using the green fluorescent protein-light chain 3 (GFP-LC3) autophagy detection platform, we found that the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(62 citation statements)
references
References 65 publications
1
60
0
Order By: Relevance
“…Chen et al [117] showed that rapamycin significantly reduced the accumulation of mutant Htt-552, and increased glutamate transporter 1 expression and [(3)H] glutamate uptake in astrocytes infected with adenovirus carrying codon gene of N-terminal 552 residues of huntingtin. Wu et al [118] showed that onjisaponin of the Radix Polygalae (Yuan Zhi) accelerated the removal of mutant huntingtin in PC12 cells by inducing autophagy via the AMPK-mTOR signaling pathway. Rose et al [119] reported that rilmenidine, a well-tolerated antihypertensive drug, attenuated signs and reduced levels of huntingtin fragments through mTORindependent autophagic pathway disease in a mouse model of HD.…”
Section: Role Of Induced Autophagy In Hdmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al [117] showed that rapamycin significantly reduced the accumulation of mutant Htt-552, and increased glutamate transporter 1 expression and [(3)H] glutamate uptake in astrocytes infected with adenovirus carrying codon gene of N-terminal 552 residues of huntingtin. Wu et al [118] showed that onjisaponin of the Radix Polygalae (Yuan Zhi) accelerated the removal of mutant huntingtin in PC12 cells by inducing autophagy via the AMPK-mTOR signaling pathway. Rose et al [119] reported that rilmenidine, a well-tolerated antihypertensive drug, attenuated signs and reduced levels of huntingtin fragments through mTORindependent autophagic pathway disease in a mouse model of HD.…”
Section: Role Of Induced Autophagy In Hdmentioning
confidence: 99%
“…Degradation of Ab and a-synuclein AD and PD [58] Rilmenidine A well-tolerated antihypertensive drug Reduction of huntingtin level through mTOR-independent autophagic pathway HD [119] Curcumin A principal component of the spice turmeric Inhibition of mTOR pathway AD and PD [23,63,103] Onjisaponin Active principle of Radix Polygalae (Yuan Zhi) AMPK-mTOR signaling pathway HD [118] Ab: b-Amyloid; AD: Alzheimer's disease; AMPK: AMP-activated protein kinase; HD: Huntington's disease; PD: Parkinson's disease.…”
Section: Expert Commentarymentioning
confidence: 99%
“…Onjisaponin B was able to induce autophagy and accelerate both the removal of mutant huntingtin and A53T '-synuclein, associated with Huntington's and Parkinson's diseases (Ling et al 2013;Wu et al 2013a) Radix Glycyrrhizae (RG) and the active constituent isoliquiritigenin RG antioxidant activity related to flavonoids and total phenolics . …”
Section: Radix Ginsengmentioning
confidence: 99%
“…Onjisaponin B was able to induce autophagy and accelerate both the removal of mutant huntingtin and A53T '-synuclein, associated with Huntington's and Parkinson's diseases (Ling et al 2013;Wu et al 2013a) Radix Glycyrrhizae (RG) and the active constituent isoliquiritigenin RG antioxidant activity related to flavonoids and total phenolics . Prevented A"(25-35)-induced neuronal apoptotic death by interfering with the increases of intracellular Ca 2C and ROS, and RG potential therapeutic for preventing the progression of AD (Lee et al 2012) …”
Section: Radix Ginsengmentioning
confidence: 99%